2016
DOI: 10.1590/2359-3997000000152
|View full text |Cite
|
Sign up to set email alerts
|

Green banana pasta diet prevents oxidative damage in liver and kidney and improves biochemical parameters in type 1 diabetic rats

Abstract: Objective: In this study, the effects of a green banana pasta diet on the oxidative damage from type 1 diabetes mellitus (DM) were investigated. Materials and methods: Formulations containing 25 (F25), 50 (F50), and 75% (F75) of green banana pasta were prepared and included in a 12-week diet of Wistar rats with alloxan-induced type 1 DM. The effects of these formulations in preventing oxidative damage in kidneys and liver homogenates of rats were evaluated using the TBARS assay (lipid peroxidation in liver) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
0
16
0
9
Order By: Relevance
“…Regarding the ingredients or foods used in the research, ten studies were conducted with green banana flour [41,43,49,50,51,52,53,55,56,59] and eight with the green banana pulp/biomass [42,44,45,46,47,48,54,60]. Most of the studies used green banana flour, probably due to the highest shelf-life and stability of the product compared to the green banana pulp/biomass [61], and this product is well characterized in the scientific literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the ingredients or foods used in the research, ten studies were conducted with green banana flour [41,43,49,50,51,52,53,55,56,59] and eight with the green banana pulp/biomass [42,44,45,46,47,48,54,60]. Most of the studies used green banana flour, probably due to the highest shelf-life and stability of the product compared to the green banana pulp/biomass [61], and this product is well characterized in the scientific literature.…”
Section: Resultsmentioning
confidence: 99%
“…However, this product tends to be expensive and not accessible in some countries [10,32,36,62,63,64,65,66,67,68,69,70,71,72], stimulating the utilization of green banana pulp/biomass in some products. Considering the type of research method, 14 of the studies were performed in vivo [41,42,44,45,46,47,48,49,51,52,54,55,59,60], one conducted in vitro [56], and three studies used both in vivo and in vitro methods [43,50,53].…”
Section: Resultsmentioning
confidence: 99%
“…Hyperglycemia in MS is associated with a large ROS generation and critical oxidative damage in various tissues, such as those of the liver. Lipid peroxidation and raised ROS have been identified as factors of decreasing antioxidant defense (Silva et al, 2016). It was demonstrated that the extreme plasma-free fatty acids and glucose levels can be related to insulin resistance (Arner, 2002, Tomas et al, 2002.…”
Section: Resultsmentioning
confidence: 99%
“…In the rats, the high level of serum HDL and low LDL is connected with the fact that in the blood cholesterol is transported mainly in high-density lipoproteins [38]. Presented in study were results of high level of HDL and low LDL + VLDL in all experimental groups that were also observed in rats of control groups in the Aberare et al [39], Kopeć et al [33] and Silva et al [40] studies. The increased concentration of glucose was observed in both groups fed diets without addition of lettuce (C and D).…”
Section: Discussionmentioning
confidence: 77%